Globalna wioska Jana Pawła II - Drążek, Dariusz (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2012)
The subject of this brief study is politics and the Catholic understanding of its object and purpose, and therefore the unjustified – although popular and widespread – claim that the Church interferes in politics may be put forward once more. In a world that boasts about the ‘achievements’ of tolerance, politics becomes a realm which the Church is excluded from. Although for the moment this is being done informally, Catholics and especially priests are ingrained with a fear of politics and anything political, whether in terms of actions or words. In this new world, politics is an important role everybody plays outside the Church. However, the Church encourages us to pursue what is good, noble and worthy of man, assuming a position “above ideologies or even defying them”. The political philosophy of the gospel is expressed in the statement: “So give back to Caesar what is Caesar’s, and to God what is God’s” (Matthew 22, 21). It clearly distinguishes between the private and the public, while not separating the two. The present paper does not attempt to present a comprehensive lecture on the social teaching of the Church, but indicates the main elements of the definition of politics, its subject, purpose and the means of achieving it. This is more of an attempt to outline the Church’s philosophy, perception and approach to politics rather than an enumeration and description of the characteristics of various areas of political activity.
John Paul II’s global village